La suspensión en prevención como medida cautelar en el proceso contencioso administrativo (2009)
The suspension in prevention, as a precautionary measure in administrative law litigation in Colombia, in its first bill was established as an action, by which, citizenswho had serious evidence that they were going to be illegal or un constitutional actions or operations to their detriment, they could prevent such actions or operations from happening by means of Administrative Law litigation. This was established byArticle 153 of the C.C.A, (Colombian Administrative Statute) included in theExtraordinary Decree 01 of 1984, in Title XVII of the provisional suspension. This tool was essentially a precautionary measure that prevented an un constitutional orillegal administrative action, not subject to any other legal action, from happening,and its purpose was to prevent any harm that would result from such action. It wasdifferent from other protection measure of temporary suspension in which theaction had already happened and such action was already producing effects.The suspension in prevention was revoked after a short period of judicial enforcement,resulting in a legal emptiness caused by the absence of this important proceduralprotection tool that allowed citizens to preventively stop administrative actionsagainst the Constitution or the law.Finally, such suspension affects the constitutional development of effective judicial protection, specifically as it relates to precautionary measures in administrative lawlitigation, issue that is to be hugely developed in the Colombian legal system.